Leveraging information and communication technology in digital economy: Exploring the contributions of the agriculture sector in Vietnam and Indonesia - Nguyễn Tô Huy; Trương Thị Hoàng Oanh; Bùi Thị Cẩm Tú; Thái Thủy Tiên; Nguyễn Hoàng Ngọc Trâm (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
The study exploits Input-Output (I-O) figures from the OECD statistical database to analyze the performance of Information and Communication Technology (ICT) applications in extending Vietnam’s digital agriculture industry. This assessment also compared Vietnam’s and Indonesia’s performance to highlight the relative ranks of the two countries. The findings show the successes and challenges of using ICT to create digital agriculture in Vietnam, with the Vietnamese government playing a pivotal role. Despite Vietnam’s enormous development potential, productivity indices remain lower than in Indonesia, showing that the current potential has been underutilized for ten years. The study also presents a detailed picture of ICT applications in digital agriculture and policy implications to encourage practitioners to become more involved. As a result, enhancing the crucial role of ICT in actively promoting Vietnam’s digital agriculture will hasten the digitization of the national sustainable wealth.